A Study of the Clinico-Bacteriological Profile of Infants Aged 29-59 Days Suffering from Very Severe Disease According to WHO IMCI Guideline - A, Rokshana; EU, Enshad; AC, Muhammad Jabed; KC , Pronab (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: According to the IMCI guidelines young infants below 2 months are considered a special group because these infants have special characteristics, that they can become sick and die very quickly from serious bacterial infections. This descriptive cross-sectional study was carried out to assess clinical characteristics of very severe disease according to WHO IMCI guideline among young infants of 29-59 days age and to determine whether clinically severe infections are associated with culture-positive bacteremia as well as to find out common etiological factors including organisms involved. The rationale behind conducting such research was that, although young infants of 29-59 days were equally vulnerable to severe infections as are the neonates; similar research addressing the condition in the young infants of the mentioned age is generally lacking. METHODS AND MATERIALS: This was a descriptive cross-sectional study conducted in the Department of Pediatrics, Chittagong Medical College Hospital, from March 2016 to September 2016. Young infants aged between 29-59 days presenting with signs of very severe disease were enrolled. Exclusion criteria were young infants with a congenital anomaly and very sick infants. RESULTS: In this study, it was observed that the majority (43.8%) of patients belonged to age 31-40 days and the mean age was 42.2 ± 7.4 days, ranged from 30 to 57 days. Regarding the sign of severe infection, the majority (97.7%) of patients had a fever, followed by 81.6% fast breathing, 65.5% history of unable to feed, 29.9% convulsion, 27.6% movement when stimulated, 18.4% grunting, and 2.3% had low body temperature. Eleven patients were found in blood culture positive. Klebsiella spp. was the most prevalent pathogens, comprising 6(54.5%) of the isolates, followed by coliform 2(18.2%), staphylococcus aureus 2(18.2%), and coagulase -ve staphylococcus was 1 (9.1%). CONCLUSION: Fever, fast breathing, and unable to feed were more common signs of very severe disease in the patients and positive blood culture was found in 12.6% of the cases. Klebsiella was found to be the commonest pathogen.